Sexual features of the old rats’ autonomic nervous system response to the development of necrotic process in heart on the background of melatonin - M. R. Khara; Z. S. Hevyk (Patologìâ)
Aim. An effect of melatonin on the autonomic regulation of the heart in terms of damage was studied in adult and old male and female rats.